Compostos de ácido hialurónico no tratamento de feridas, revisão - Tiago Daniel Moreira Fernandes (2022)
The skin is the main barrier of defense against infections. After the skin is damaged by an external agent, a complex process with a goal of repairing the damaged area is started. To achieve a faster and more favorable healing of skin lesions, different biomaterials have been created, among these, are sponges, hydrogels and electro spun membranes. Different polymers have been used for the preparation of these biomaterials, among which, is Hyaluronic Acid, an extracellular matrix compound with anti-aging effects and hydrating properties, making it an extremely efficient molecule for biomedical usage. Our goal is to provide is a short overview of the different HA-based wound dressings that are being tested in vivo.